Postpartum depression and associated factors among childbearing women from the recent Demographic and Health Survey data of Mozambique: Multilevel analysis - Mamaru Melkam; Bezawit Melak Fente; Yohannes Mekuria Negussie; Zufan Alamrie Asmare; Hiwot Altaye Asebe; Beminate Lemma Seifu; Alemayehu Kasu Gebrehana; Sintayehu Simie Tsega; Meklit Melaku Bezie; Angwach Abrham Asnake (Heliyon)
Introduction: Postpartum depression is a non-psychotic depressive illness that affects women who have recently given birth. Symptoms of the illness include thoughts of suicide, low self-worth, guilt about not being able to care for their newborn, blaming themselves thoughts, and nervousness. Despite there being many studies conducted at the hospital level there are limited studies conducted at the national level to determine the individual and community level factors. Depression during childbirth can have several detrimental effects, including increased risk of complication and decreased satisfaction with birth, decreased trust in medical facilities, and decreased women's participation in maternity and newborn healthcare units.Therefore, this study amid to reveal the prevalence of postpartum depression and associated factors at individual and community levels among women who give birth in Mozambique's recent data Demographic and Health Survey (DHS). Method: Multilevel logistic regression analysis was carried out from the recent Demographic and Health Survey data. A total of 5,468 sample sizes of Mozambique DHS data were used for this secondary data analysis. At individual and community level factors were assessed to determine the burden of postpartum depression at a p-value of 0.05 with a 95 % CI with AOR. Results: The prevalence of postpartum depression among women who give birth from the recent Mozambique DHS data was 24.60 % with a CI of 23.47 %–25.75 %. No education [AOD = 1.37: 95 % CI; (1.26, 1.68)] at individual level and [AOR = 3.14:95 % CI; (2.39, 5.18)] at the community level, widowed/divorced [AOR = 1.73: 95%CI; (1.14, 3.61)], and No occupation [AOR = 1.35:95 % CI; (1.19, 1.64)] were the associated variables with postpartum depression. Conclusion: Nearly three women out of ten women who give birth develop postpartum depression. Low education status, widowed/divorced, and no occupation were the associated factors with postpartum depression. Therefore, enhancing education, creating job opportunities, and keeping married will reduce the burden of postpartum depression. This study indicates maternal depression post-delivery should be given attention by the National Health Office and other police makers. Educational level should be improved to have a continuous and sharp change in maternal depression after delivery.